Association between dietary inflammatory index and Parkinson’s disease: a prospective study of 165,531 UK biobank participants - Chen-wei Hao; Dong-rui Ma; Zheng-wei Hu; Xiao-yan Hao; Meng-jie Li; Meng-nan Guo; Shuang-jie Li; Chun-yan Zuo; Yuan-yuan Liang; Zhi-yun Wang; Yan-mei Feng; Cheng-yuan Mao; et al. (Scientific Reports)
Abstract Parkinson’s disease (PD) is a common neurodegenerative disorder that increasingly affects the aging population. Inflammation is implicated in both the onset and progression of PD, with diet influencing inflammatory pathways. The Dietary Inflammation Index (DII) measures diet-related inflammatory potential. This study aimed to assess the relationship between DII and PD. Using data from the UK Biobank, which included 165,531 participants, Cox proportional hazards models were applied to examine the association, adjusting for various covariates. During the study, 934 participants (0.6%) developed PD. While univariable analysis identified significant associations between PD risk and factors such as age, sex, smoking history, diabetes, hypertension, and education. But both univariable and multivariable analyses demonstrated consistent findings, with results across models indicating no significant association between the DII and PD risk. These findings align closely with the null hypothesis, though they do not definitively exclude the possibility of a clinically meaningful relationship due to potential limitations such as residual confounding or statistical power constraints. Further studies are needed to explore the complex relationship between diet and PD, offering insights into prevention and intervention strategies.